Impact of bowel resection margins in node negative colon cancer. - Rocha, R (2016)
Surgical intestinal resection margins in colon cancer are a longstanding debate in terms the optimal distance between the tumor and the colonic section line. The aim of this study is to define the oncological outcomes in relation to surgical margins, measured in terms or recurrence rate, time-to-recurrence, disease-free survival and overall survival in a population of node negative colon cancer patients. METHODS: We conducted a retrospective observational longitudinal single institution study. All patients submitted to colon cancer surgery between January 2006 and December 2010 were analyzed. Only node negative patients were included in the study, with analysis of 215 patient charts, divided in two groups (Intestinal margin lower than 5 cm-group 1; and 5 cm or higher-group 2). RESULTS: Mean age of patients was 70.4 years (±11.7), with a male predominance (57.7%). Group 2 more frequently corresponded to Stage II (83 vs 71%; p = 0.05). Global mean total lymph nodes harvested were 12, and were higher in group II than in group I (13.8 ± 8.2 vs 10.4 ± 5.7; p = 0.001). In terms of time-to-recurrence patients of group 2 had longer time than patients of group 1 (32.3 ± 12.1 vs 21.8 ± 13.8 months; p = 0.03), as well as a lower recurrence rate in group I (13.7 vs 17.2%), despite not statistically significant. CONCLUSIONS: This study has showed that patients with 5 cm or higher bowel resection margins had longer time-to-recurrence that was statistically significant. Recurrence rates were lower in the group of patients with longer surgical margins, however not statistically significant.